Anticholinergic effect on cognition (AEC) of drugs commonly used in older people. (9th June 2016) - Bishara, Delia; Harwood, Daniel; Sauer, Justin; Taylor, David M.
Abstract : Objective: Use of anticholinergic drugs in older people is associated with increased risk of cognitive decline and of dementia and death. Method: We identified drugs widely used in older people and attempted to classify their anticholinergic effect on cognition (AEC) according to our three‐point scale which scored AEC according to in vitro anticholinergic potency, capacity to cross the blood–brain barrier and statements made in standard texts. Results: In total, 165 drugs were examined. We identified 21 drugs with an AEC score of 3, 18 with a score of 2, 21 with a score of 1 and 62 with a score of 0. Owing to insufficient information, we were unable to classify 43 drugs. Conclusions: A large number of drugs commonly used in older people are likely to be associated with cognitive impairment. Copyright © 2016 John Wiley & Sons, Ltd.